2017
DOI: 10.1177/2473974x16685692
|View full text |Cite
|
Sign up to set email alerts
|

NSQIP as a Predictor of Length of Stay in Patients Undergoing Free Flap Reconstruction

Abstract: ObjectiveThe National Surgical Quality Improvement Program (NSQIP) calculator was created to improve outcomes and guide cost-effective care in surgery. Patients with head and neck cancer (HNC) undergo ablative and free flap reconstructive surgery with prolonged postoperative courses.MethodsA case series with chart review was performed on 50 consecutive patients with HNC undergoing ablative and reconstructive free flap surgery from October 2014 to March 2016 at a tertiary care center. Comorbidities and intraope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…With these complications, they require more complex care and thus pose an increased burden on the health care system. These patients consume more hospital and physician resources than patients who undergo other otolaryngological surgeries . Several studies have shown differences in HNC patient outcomes based on hospital characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With these complications, they require more complex care and thus pose an increased burden on the health care system. These patients consume more hospital and physician resources than patients who undergo other otolaryngological surgeries . Several studies have shown differences in HNC patient outcomes based on hospital characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…These patients consume more hospital and physician resources than patients who undergo other otolaryngological surgeries. 35 Several studies have shown differences in HNC patient outcomes based on hospital characteristics. Eskander et al 36 concluded that a volume-outcome relation exists for HNCs, with high-volume hospitals having better overall survival than low-volume hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…15 Additionally, Riley et al showed that the SRC was an inadequate predictor of LOS in patients undergoing any head and neck free flap surgery. 18 Ma et al analyzed 561 head and neck free flaps and found that, although SRC demonstrated a Brier score <0.01 for urinary tract infection and renal complications, no complications were associated with a C statistic >0.8 indicating inadequate test performance. Furthermore, LOS was not accurately predicted by the SRC in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Although not formally in the current study, length of hospital stay has also been significantly underpredicted in numerous recent studies. [23][24][25] All of the 30-day outcomes evaluated here have been highly studied and offer significance in numerous ways. Venous thromboembolism and cardiopulmonary complications put patients at risk for sudden decompensation and death.…”
Section: Surgical Risk Calculator Predictive Accuracymentioning
confidence: 99%